Ayurverdic management of the lifestyle disorders - Surve, Pankaj; Sanjay Lungare (Ayurline: International Journal of Research in Indian Medicine, 2025)
Ayurveda is ancient science of life that aims to maintaining the healthy life as well as preventing the disease for the benefit of human beings. It has proven its importance from time immortal. Medoroga and Prameha a is one of the lifestyle disorders characterised by deposition of meda dhatu (excess fat) into the body and excessive urination along with meda and kleda respectively. According to National Institute of Nutrition, Hyderabad, about 20.7% and 26.3 % of women and men respectively were found to be overweight, in India during 2015-16. Even advance countries are suffering from the comorbid conditions related to unhealthy life style. These disorders are more effectively defined by assessing its linkage to morbidity and mortality. It is clearly visible that in the Ayurveda and modern science both mentioned the nearabout same characteristics in case of Obesity and Diabetes. Unknowingly following repeated unhealthy life style leads to such diseases. These disorder can be manged by following proper Aahar-vihar, Panchakarma, Rasayan therapy and usage of some herbs acting as immunomodular, adaptogenic , antioxidant, hyperlipidemic. Immunomodulatory drugs modify the response of the immune system by increasing or decreasing the production of serum antibodies. Adaptogens help the body to adapt stress, These drugs has proven its efficacy in the present pandemic situation of covid. Antihyperlipidemic drugs reduces elevated levels of LDL and decreased level of HDL in the blood. Hyperlipidemia if not managed increases risk of coronary heart disease and atherosclerotic heart disease. Antilipidemic herbs are found effective with any untoward side-effects.